Governance-Driven Solutions for Women’s Empowerment in the Mining Sector: Tackling Gender Inequality through Inclusive Policies - Ikhsan Ikhsan; Vellayati Hajad; Ilham Mirza Saputra; Herizal Herizal; Ikhwan Rahmatika Latif (Journal of Contemporary Governance and Public Policy, 2025)
This research examines governance strategies to address gender inequality in the mining industry and enhance women’s empowerment. It identifies barriers preventing women from accessing opportunities and leadership roles through a systematic review of 37 articles published between 2014 and 2024. Data analysis using NVivo 12 Plus focused on themes such as women’s roles, challenges, and gender dynamics, while VOSviewer was employed for bibliometric analysis. The findings reveal systemic barriers, including limited training, unequal pay, and exclusion from decision-making. The study underscores the need for inclusive policies and gender-sensitive governance to drive meaningful change, aligning with the Sustainable Development Goals (SDGs), particularly gender equality (SDG 5) and decent work and economic growth (SDG 8). It calls for comprehensive policies, comparative analyses of effective strategies across contexts, and integration of community perspectives into empowerment initiatives. Strengthening governance frameworks and fostering collaboration between stakeholders, policymakers, and local communities can enhance gender equality and inclusive growth in mining. Future research should further explore policy effectiveness, cross-national comparisons, and innovative governance models to address structural inequalities and promote sustainable economic participation for women.